Quantitative Evaluation of Pulsed Thermography, Lock-in Thermography and Vibrothermography on Foreign Object Defect (FOD) in CFRP - Bin Liu; Hai Zhang; Henrique Fernandes; Xavier Maldague (Sensors, 2016)
In this article, optical excitation thermographic techniques, including pulsed thermography and lock-in thermography, were used to detect foreign object defect (FOD) and delamination in CFRP. Then, vibrothermography as an ultrasonic excitation technique was used to detect these defects for the comparative purposes. Different image processing methods, including cold image subtraction (CIS), principal component thermography (PCT), thermographic signal reconstruction (TSR) and Fourier transform (FT), were performed. Finally, a comparison of optical excitation thermography and vibrothermography was conducted, and a thermographic probability of detection was given.